1968
DOI: 10.1677/joe.0.0400015
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Defect of Adrenocortical Control in Cushing's Disease

Abstract: SUMMARY The plasma sugar, 11-hydroxycorticosteroid, and growth hormone responses to insulin have been studied in patients with Cushing's disease. They showed an impaired or absent plasma 11-hydroxycorticosteroid and growth hormone rise during the test, as compared with control subjects, despite the injection of amounts of insulin which produced a similar degree of hypoglycaemia. This test proved of value in differentiating between these patients and those with 'simple ' obesity since the latter usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…12) first, in patients with acromegaly, whose response to metyrapone was clearly exaggerated while the response to hypoglycemia was subnormal (not because inadequate hypoglycemia was induced); second, in patients with hypercortisolism who sometimes manifested excessive responses to metyrapone and usually, but not always, responded subnormally to the hypoglycemic stimulus; and third, in patients with hyperprolactinemia (with or without known tumors) whose metyrapone response was unrelated to the level of baseline cortisol production and whose cortisol/glucose slope after hypoglycemia was significantly increased. Except for the abnormalities in patients with Cushing's syndrome which have been documented previously (95)(96)(97)(98), these discordant parameters of HPA function have not been clearly delineated in the past and their mechanism is unknown. It is perhaps relevant that L-dopa administration has been found to inhibit cortisol release in response to stress in dogs (99).…”
Section: Discussionmentioning
confidence: 99%
“…12) first, in patients with acromegaly, whose response to metyrapone was clearly exaggerated while the response to hypoglycemia was subnormal (not because inadequate hypoglycemia was induced); second, in patients with hypercortisolism who sometimes manifested excessive responses to metyrapone and usually, but not always, responded subnormally to the hypoglycemic stimulus; and third, in patients with hyperprolactinemia (with or without known tumors) whose metyrapone response was unrelated to the level of baseline cortisol production and whose cortisol/glucose slope after hypoglycemia was significantly increased. Except for the abnormalities in patients with Cushing's syndrome which have been documented previously (95)(96)(97)(98), these discordant parameters of HPA function have not been clearly delineated in the past and their mechanism is unknown. It is perhaps relevant that L-dopa administration has been found to inhibit cortisol release in response to stress in dogs (99).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any such changes in subjects with pituitarydependent Cushing's syndrome has also been observed previously. The phenomenon has been attributed by some to an intrinsic hypothalamic defect of the disease (James, Landon, Wynn & Greenwood, 1968), and by others to adrenocortical overactivity (Werder, Smilo, Hane & Forsham, 1971). The latter view is supported by the recent observations of Besser, Cryer & Staub (1972) that such patients do show an in¬ crease of plasma ACTH concentration during insulin-induced hypoglycaemia after adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, definite proof of the diagnosis, such as histological verification of the tumour or cure by surgical re¬ moval, was often lacking, especially in the case of Cushing's disease. Although false positive (9,20,29,30) and false negative responses (8,31) have been reported, their incidence is therefore difficult to evaluate. However, Kuhn et al (21) have recently reported a response of plasma ACTH and lipotropin after LVP injection in only 26 of 41 patients with proven Cushing's disease.…”
Section: Crh Testmentioning
confidence: 99%